The Impact of the Concept of Public Relations on the Organizational Performance in the Telecommunications Sector in Sudan. (A case study of Sudan Telecommunications Co., Ltd) - Ahmed, Alsadig Mohamed (Journal of Economic, Administrative and Legal Sciences, 2020)
The study aimed at knowing the attitudes of the administrative leaders towards the concept of public relations from its various administrative, organizational, and functional aspects. To achieve this goal the study followed the descriptive-analytical approach. The research hypotheses model was adopted based on what the study said. For the nature of the study, the intention sample was adopted as a questionnaire was designed to collect data. A total of 150 questionnaires were distributed, of which 100 were recovered at a recovery rate of 67% and to ascertain the degree of reliability in the data, the (t- f) test was used to prove the hypotheses. One of the most important findings of the study is the lack of clarity of the concept of public relations in the communications sector in Sudan. This has led to the overlapping work of the departments with each other. As well as the lack of understanding of the functions of public relations functions, the administrative leadership also failed to understand the functions of public relations, which led to the weakness of the effectiveness of the institution by conducting research and planning. The study recommended a review of the regulations governing public relations work in public institutions and private sector companies by formulating them by specialists and experts in public relations to determine their functions accurately and their relationships with other jobs. The study dealt with the relationship between the concept of the organizational status of public relations management and performance in the telecommunications sector in Sudan. The importance of the study was to identify the importance of the administrative functions of public relations in the institutions, which are planning, organizing and conducting research in order to improve the work environment and strengthen social ties between members of the organization.